Self-concept of early and middle adolescents belonging to single parent and two parent families a comparative study - Calma, Ana C.
This research is a comparative study on the self-concept of students belonging to single-parent and two-parent families. The participants are first year to fourth year high school students enrolled in an exclusive school in Metro Manila. The ages of the students are 13 to 16 years old. The method of selection is purposive sampling: that the participants come from single parent and two-parent families; the single parent families are headed by mothers due to separation; and the two parent families have both parents in the household; there is an equal number of participants per type of family, that the age (13-14 &15-16 years old) of the participants per type of household is equal. The number of sample is 80 students (40 students per type of family). Results suggested that interaction effects were present between the variables age and type of household--single parent and two-parent families based on the Pasao Self-concept Scale scores and the Piers-Harris Self-concept scores. The 13-14 year olds belonging to two-parent families. While, the students, age 15-16 years old belonging to two parent families have higher self-concept than the students, age 15-16 years old from single-parent families. One of the conclusions of the present study was the participants age 13-14 years old from single-parent families may have higher self-concept because their parents especially their mothers manifest compensatory mechanisms or forms of coping due to the kind of family structure they have. On the other hand, the participants age 15-16 years old belonging to two parent families may have higher self-concept because coming from intact family is desirable since they are in the stage of being conscious on the norms and cultural standards. The 1987 constitution and other legislation recognize that Filipino intact families that are well-functioning and happy families constitute the necessary foundation for social stability, economic progress and development. One of the recommendations of the present study was parents remain to be responsible, supportive and should be good role models to their children for they are very influential in the development of a positive self-concept. And also, grandparents, relatives, teachers, and guidance counselors have the role of being second parents. They should have communication with their grandchildren, nephews/nieces, and students and they should be good role models as they are also influential in developing a positive self-concept.